Genome-wide association analysis of eggshell pore traits based on whole genome resequencing - Zhang, Jun-Jie; Chen, Yi-Fan; Shi, Lei; Wang, Yi-Tong; Zhao, Xiao-Yu; Zhou, Rong-Yan; Chen, Hui; Liu, Hua-Ge; Ning, Zhong-Hua; Wang, De-He (Frontiers in Animal Science, 2024)
Eggshell pores can be subdivided into micrometer-scale gas pores, submicroscopic bubble pores, and nanoscale mesopores. All are important indicators of eggshell quality ensuring gas exchange between the inside and outside of the eggshell and preventing invasion by external bacteria. Although previous studies on eggshell pores focused on gas pores, recent studies have shown that bubble pores may play an more important role in regulating gas exchange. In order to investigated the relationship between gas and bubble pores and the mechanisms of genetic regulation. In this study, 40-week-old Brown-Egg Dwarf Layers (DWL) eggs were selected, and the quantity of gas pores (QGP), quantity of mammillary (QM), and quantity of bubble pores (QBP), area sum of bubble pores (ASBP), and other bubble pore-related indexes were determined. The correlation between each index was calculated, and genome-wide association analysis (GWAS) was performed based on whole genome resequencing (WGR). The results showed that the CVs of QGP and QM were 15.69% and 15.49%, respectively, and the CVs of the related pore indices, such as QBP and ASBP, were 29.22%-44.82%. The correlation coefficient between QGP and QM was 0.59 (P< 0.01), and there was no correlation between QGP, QM, and the bubble pore-related indicators (P > 0.05). These results above suggest that the gas and bubble pores may be two independent pore systems. A total of 32 single nucleotide polymorphisms (SNPs) associated with the suggestively significant level of bubble pore correlation indexes were detected in GWAS, and the corresponding genes were ANXA10, CDH10, AADAT, RXFP1, FNIP2, DDX60, PCDH10, RAPGEF2, FSTL5 and SPOCK3. KEGG enrichment analysis showed that these genes were mainly expressed in the calcium ion binding pathway, indicating that the genes and pathways may play a regulatory role in forming bubble pores during eggshell calcification. This study provides a basis for revealing the genetic regulatory mechanism of eggshell pores and a reference and direction for further improvement in eggshell quality.